A comparative study of efficacy of intravenous dexmedetomidine with perineural dexmedetomidine as adjuvant to ropivacaine in supraclavicular brachial plexus block in upper limb surgery - Roy, Nabanita; Md. Babrak Manuar; Roy, Moumita; Bimal Kumar Hajra (Asian Journal of Medical Sciences, 2024)
Background: In supraclavicular brachial plexus block, to prolong the duration of analgesia, many adjuvants have been tried in the past in many studies but an ideal adjuvant remains yet to be discovered. Dexmedetomidine, a selective Alfa-2 adrenergic agonist when added to local anesthetic has been reported to prolong the block duration and post-operative analgesia in various regional blocks. Aims and Objectives: The aims and objectives are to study the onset and duration of sensory and motor blockade, postoperative analgesia, and hemodynamic effects of addition of dexmedetomidine with ropivacaine in supraclavicular brachial plexus block. Materials and Methods: Sixty patients aged between 18 and 60 years, American Society of Anesthesiologists class I and II, of both sexes, scheduled for upper limb surgery under supraclavicular brachial plexus block were randomly allocated into 2 groups. Group-A received 20 mL of 0.5% ropivacaine in brachial plexus block with 1 μg/kg dexmedetomidine as adjuvant perineurally and Group-B received 20 mL 0.5% ropivacaine in brachial plexus block with dexmedetomidine intravenous infusion at 1 μg/kg over 10 min. Intraoperatively non-invasive blood pressure, heart rate, SpO2, and sedation were recorded every 5 min for the first 10 min and every 15 min thereafter till the end. Time of first rescue analgesic, intensity of postoperative pain, and total analgesic required were recorded. Results: Onset of sensory and motor block was faster in Group-A than Group-B. Duration of analgesia was prolonged in Group-A than Group-B. Hemodynamic stability was better maintained in Group-A than Group-B. Sedation was better in Group B. Conclusion: Dexmedetomidine as adjuvant to ropivacaine in supraclavicular brachial plexus block is more efficacious in providing faster onset of motor and sensory blocks and prolonging duration of postoperative analgesia with better hemodynamic stability.